Bacterial enzymes as potential feed additives in poultry farming - A.O. Koryagina; D.S. Bul'makova; A.D. Suleimanova; N.L. Rudakova; A.M. Mardanova; S.Y. Smolencev; M.R. Sharipova (Учёные записки Казанского университета: Серия Естественные науки)
The problem of obtaining economic benefits in poultry breeding from complete absorption of feeds by domestic fowls through increasing the digestibility of nutrients remains urgent. The addition of exogenous enzymes to broiler rations enhances the energy and protein intake by improving the substrate bioavailability. The presence of antinutritional dietary factors in poultry feeds (non-starch polysaccharides, protease inhibitors, lectins, and phytates) indicates the possibility of using exogenous enzymes. We assessed the potential of histidine acid phytase Pantoea sp. 3.5.1 and subtilisin-like proteinase B. pumilus as feed additives. When the enzymes pass through the digestive tract, they are exposed to elevated body temperatures of the fowl (40 ?C), pH changes in different parts of the digestive tract, and the influence of bile. Thus, it was important to study the stability of the enzymes under these conditions. It was shown that proteinase maintains its activity throughout the gastrointestinal tract of the fowl: in a weakly acidic environment (pH 5.5, goiter), the enzyme activity remained full (100%); at pH 2.9 (stomach), its decreased by 40%; and under the alkaline conditions of pH 6.5–8.0 (small and large intestine), its values were restored and increased by 13% relative to the control group. When exposed to bile at the concentrations from 0.01% to 0.25% for 1 h, phytase retained more than 50% of its activity (p < 0.05). At the concentrations of bile from 0.01% to 0.05% (1-h exposure), the activity of proteinase remained at the control level. The data obtained show that microbial enzymes in the digestive tract of domestic fowls retain catalytic activity. In the course of the balance experiment, the group of chickens treated with proteinase at the concentration of 10 U/kg demonstrated the highest nitrogen and calcium digestibility coefficients (56.4% and 59.5%, respectively). The use of phytase (1000 U/kg) had a significant impact on the absorption of phosphorus (the digestibility coefficient was 40.5% (0.30 g)). Thus, B. pumilus proteinase and Pantoea sp. 3.5.1 phytase have the potential to be used as feed additives for chickens.